Validation of the Malay Version of the Parental Bonding Instrument among Malaysian Youths Using Exploratory Factor Analysis - Muhammad, NA; Shamsuddin, K; Omar, K; Shah, SA; Amin, RM (Univ Sains Malaysia, Sch Medical Sciences, 2024)
Indexed by Scopus/WOS